Long-distance mobility in the North-Western Mediterranean during the Neolithic transition using high resolution pottery sourcing. (December 2019) - Gabriele, Marzia; Convertini, Fabien; Verati, Chrystele; Gratuze, Bernard; Jacomet, Suzanne; Boschian, Giovanni; Durrenmath, Gilles; Guilaine, Jean; Lardeaux, Jean-Marc; Gomart, Louise; Manen, Claire; Binder, Didier
Highlights: High potential of multi-analytical approach to pottery sourcing. Geochemical proxies precisely circumscribe the source area for pottery raw material. Results provide evidence for Neolithic interregional networks. Unexpected milestone in the first Neolithic migration in the NW Mediterranean. Abstract: The Neolithisation of the North-Western Mediterranean is still an open issue. New data has recently enriched the chronological and cultural archaeological framework, providing more precise absolute dates and revealing a new and more complex process of expansion of farming in Southern Europe. The Mediterranean route of colonization (6000–5600 BCE), is characterized by the so-called Impressed Wares (IW) or Impresso-Cardial Complex (ICC) which demonstrate huge internal diversity in material culture, notably in pottery style and technology. This polythetic imprint of the ICC is intimately linked to dynamics of raw material exploitation (such as obsidian) and interconnections within circulation and exchange networks of goods. Through a comparative and multi-analytical approach to pottery characterization of entire assemblages from two distant sites in the North-Western Mediterranean, each characterized by predominantly local pottery production, we demonstrate long-distance mobility of non-local pottery vessels from the Tyrrhenian regions towards the Languedoc (up to 1000 km) during the Neolithic transition. Our study allows us to highlight this unexpected milestone in the first Neolithic migration in the North-Western Mediterranean.